Covalent layer-by-layer assembly of hyperbranched polymers on alginate microcapsulesto impart stability and permselectivity - Gattás-Asfura, KM (J Mater Chem B Mater Biol Med, 2014)
The microencapsulation of cells has shown promise as a therapeutic vehicle for the treatment of a wide variety of diseases. While alginate microcapsules provide an ideal cell encapsulation material, polycations coatings are commonly employed to enhance stability and impart permselectivity. In this study, functionalized hyperbranched alginate and dendrimer polymers were used to generate discreet nanoscale coatings onto alginate microbeads via covalent layer-by-layer assembly. The bioorthogonal Staudinger ligation scheme was used to chemoselectively crosslink azide functionalized hyperbranched alginate (alginate-hN(3)) to methyl-2-diphenylphosphino-terephthalate (MDT) linked PAMAM dendrimer (PAMAM-MDT). Covalent layer-by-layer deposition of PAMAM-MDT/alginate-hN(3) coatings onto alginate microbeads resulted in highly stable coatings, even after the inner alginate gel was liquefied to form microcapsules. The permselectivity of the coated microcapsules could be manipulated via the charge density of the PAMAM, the number of layers deposited, and the length of the functional arms. The cytocompatibility of the resulting PAMAM-MDT/alginate-hN(3) coating was evaluated using a beta cell line, with no significant detrimental response observed. The biocompatibility of the coatings in vivo was also found comparable to uncoated alginate beads. The remarkable stability and versatile nature of these coatings provides an appealing option for bioencapsulation and the release of therapeutic agents.